2008
DOI: 10.1016/j.cplett.2008.08.039
|View full text |Cite
|
Sign up to set email alerts
|

Challenge in understanding size and shape dependent toxicity of gold nanomaterials in human skin keratinocytes

Abstract: As the nanotechnology field continues to develop, assessing nanoparticle toxicity is very important for advancing nanoparticles for biomedical application. Here we report cytotoxicity of gold nanomaterial of different size and shape using MTT test, absorption spectroscopy and TEM. Spherical gold nanoparticles with different sizes are not inherently toxic to human skin cells, but gold nanorods are highly toxic due to the presence of CTAB as coating material. Due to CTAB toxicity, and aggregation of gold nanomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
230
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 322 publications
(246 citation statements)
references
References 29 publications
16
230
0
Order By: Relevance
“…Similar results were obtained for 3 nm AuNPs, 5nm, 5, 12, 20, 30, 50, and 70nm, 3, 5, 8, 12, 17, 37, 50, and 1200nm, 4 and 13nm, and 40nm 112 [53][54][55][56][57][58]. Taking into account the abovementioned data, it could be possible to expand the boundaries to both the lower level (to 3 nm) and larger particles up to 100 nm to avoid a toxic AuNP effect, if we are considering a limited dose of about 10 12 particles/ml.…”
Section: Particle Size Effectsupporting
confidence: 74%
See 1 more Smart Citation
“…Similar results were obtained for 3 nm AuNPs, 5nm, 5, 12, 20, 30, 50, and 70nm, 3, 5, 8, 12, 17, 37, 50, and 1200nm, 4 and 13nm, and 40nm 112 [53][54][55][56][57][58]. Taking into account the abovementioned data, it could be possible to expand the boundaries to both the lower level (to 3 nm) and larger particles up to 100 nm to avoid a toxic AuNP effect, if we are considering a limited dose of about 10 12 particles/ml.…”
Section: Particle Size Effectsupporting
confidence: 74%
“…Nanoparticles have high surface-to-volume ratios when compared with large particles and are usually smaller than several hundred nanometers in size, comparable to large biological molecules, of a size about 100 to 10,000 times smaller than human cells. The range of studied gold nanoparticles covers more than two orders of magnitude from the minimal size of 1.0, 1.2 or 1.4 nm (atomic cluster Au 15 , Au 35 or Au 55 ) [2] to the maximal size of 250 nm [3].…”
Section: Introductionmentioning
confidence: 99%
“…The template was removed with a methanol acidic wash because CTAB has been shown to be toxic for cells 41 due to its capability to damage biological membranes and cause the release of intracellular enzymes. The effective removal of CTAB was confirmed with FT-IR ( Figure 1A and B).…”
Section: Characterization Of Msnpsmentioning
confidence: 99%
“…These fine particles have unique properties that make them biologically active with affinity to accumulate in the vital organs mainly kidney liver and spleen [3][4][5] . Previous research work demonstrated the potential toxic effect of GNPs due to their size, surface area, shape, and charge where smaller particles are more toxic than the larger ones [6][7][8] . GNPs demonstrated oxidative stress and macromolecules interaction that could result in histocytotoxicity [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%